Antiresorptive therapy and risk of mortality and refracture in osteoporosis-related hip fracture: a nationwide study. Issue 1 (January 2016) - Brozek, W.; Reichardt, B.; Zwerina, J.; Dimai, H.; Klaushofer, K.; Zwettler, E.
Abstract Summary We analyzed the association of bisphosphonate therapy with mortality and hip refracture incidence among osteoporosis-related hip fracture patients in Austria. Mortality was lower in primarily female bisphosphonate users, while hip refracture incidence was generally elevated relative to controls, indicating beneficial effects of bisphosphonates other than on bone. Introduction The purpose of this study was to analyze mortality and hip refracture risk in osteoporotic hip fracture patients with and without antiosteoporotic medication. Methods We retrospectively analyzed data on 31, 668 Austrian patients ≥50 years with a hip fracture between July 2008 and December 2010 for antiosteoporotic drug treatment with respect to outcome parameters all-cause mortality, hip refracture incidence, and hip refracture-free days. Outcomes when bisphosphonate (BP) treatment was begun before or after fracture were compared with an age- and sex-matched hip fracture control without antiosteoporotic medication. Results 27.69 % of patients (33.01 % of women, 13.13 % of men) were prescribed antiosteoporotic medication, primarily BPs. Females having initiated BP treatment before first fracture had lower odds for mortality 1 and 3 year(s) post-fracture, whereas hip refracture incidence under pre-fracture BP initiation was generally higher. Treatment that was started after fracture, however, entailed significantly lower mortality hazards for both genders (HR 0.43, 95 %CI 0.36–0.52, p  < 0.0001 after 1 year) but significantly higher hip refracture incidence except for patients aged 50–69 years and more hip refracture free days for females. Hip refractures overall amounted to 29.22/1000 patient years differing significantly between women and men (31.03 vs. 23.89, respectively, p  < 0.0001), and longer hip refracture free survival was observed for women than for men (499 vs. 466 median days, respectively, p  < 0.0001). Conclusions Although BP use is associated with reduced mortality after hip fracture, notably among women, hip refracture incidences are likewise elevated, which is most likely accounted for by a high probability of BP prescription to more comorbid patients suffering from more severe osteoporosis. Concomitantly, through possible effects other than on bone, BPs might be able to curtail mortality. Male hip fracture patients' low treatment frequency in particular reflects underdiagnosis and undertreatment of osteoporosis in Austria.